2018
DOI: 10.1021/acssuschemeng.8b05323
|View full text |Cite
|
Sign up to set email alerts
|

Development of Adsorbents for Selective Carbon Capture: Role of Homo- and Cross-Coupling in Conjugated Microporous Polymers and Their Carbonized Derivatives

Abstract: Selective adsorption of CO2 from natural gas results in increased calorific value, decreased gas volume, and reduced corrosion. For this purpose, the development of high-performance adsorbents with regard to both adsorption capacity and CO2/CH4 selectivity receives great attention. Herein, two new conjugated microporous polymers (CMPs) were prepared by Yamamoto homocoupling and Sonogashira–Hagihara cross-coupling reaction. The significant role of homo- and cross-coupling in CMPs in selective CO2 separation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…For example, microporous carbon derived from pyrolysis of mesitylene-based polymer and NUT-15 polymer adsorbs 6.16 and 5.4 mmol of CO 2 g −1 at 0 °C and 1 bar which is far less than the CO 2 adsorption for LSB1-800 under similar conditions. 37,38 For LSB1-800, the contribution of micropores to the total surface area and total pore volume are 87% and 81%. The presence of narrow micropores results in enhanced interactions between the adsorbent and adsorbate at low pressures.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…For example, microporous carbon derived from pyrolysis of mesitylene-based polymer and NUT-15 polymer adsorbs 6.16 and 5.4 mmol of CO 2 g −1 at 0 °C and 1 bar which is far less than the CO 2 adsorption for LSB1-800 under similar conditions. 37,38 For LSB1-800, the contribution of micropores to the total surface area and total pore volume are 87% and 81%. The presence of narrow micropores results in enhanced interactions between the adsorbent and adsorbate at low pressures.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…20 In the past few years, many CMPs and HCPs with tunable nanopores, [21][22][23][24] various functional units [25][26][27][28][29][30] and a wide range of raw materials, [31][32][33] have been prepared. Additionally, to further improve the CO 2 uptake of these polymers, some commonly modified methods have been developed including carbonization, [34][35][36][37] post-functionalization [38][39][40][41] and composite processes. 42 However, CMPs and HCPs are still limited by the synthetic issue of the low surface area, which also brings about a large barrier to CCS technologies.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, the effect of KOH-activation and activation temperature is discussed. 16 Thermal study demonstrates that NUT-16 has high yield in nitrogen than in air atmosphere. In nitrogen, NUT-16 predominantly decomposes at approximately 450 °C.…”
Section: ■ Resultsmentioning
confidence: 98%
“…It has been reported that the presence of heavy metals such as Sn significantly enhances the thermal stability of polymers than their analogues without heavy metals, leading to high carbonization yield of porous carbons . In addition, the effect of KOH-activation and activation temperature is discussed . Thermal study demonstrates that NUT-16 has high yield in nitrogen than in air atmosphere.…”
Section: Resultsmentioning
confidence: 99%